Nurses' experience of integrating evidence‐based changes into their practice: A qualitative study - Homeira Khoddam; Mahnaz Modanloo; Neda Mehrdad; Fatemeh Heydari; Razieh Talebi (Wiley, 2023)
Abstract Aim To explore the experiences of neonatal and NICU nurses on participating in evidence‐based changes in their neonatal pain management practice. Design It is a qualitative conventional content analysis. Methods A purposive sample with nurses working in neonatal and NICUs was used. The data were collected through 11 semi‐structured in‐depth individual interviews, five focused group discussions, and observations and analyzed using the conventional content analysis method based on the Elo and Kyngäs model. The COREQ checklist was used for writing the report. Results Analysis of gathered data led to the emergence of four themes, including 'being in a supportive and encouraging atmosphere', 'a journey from resistance to adherence', 'achieving multi‐dimensional improvements', and 'facing obstructive challenges'.